Dansk serielyrik: Æstetikteoretiske og litteraturhistoriske perspektiver på en poetisk strømning - Stein Larsen, Peter (Passage - Tidsskrift for litteratur og kritik, 2018)
The article examines the serial trend in modern poetry. The characteristics of serial poetry are distinguished on three levels, namely the parts of the work, the work as a whole and a series of works. The article investigates an analytical and an interpretative strategy that can be applied to serial poetry. The theory of the serial and serialization is confronted with examples from Danish contemporary poetry.